Characterization and antimicrobial activity of microencapsulated citral with dextrin by spray drying - Yoplac, Ives (2021)
This work was supported by Fondo Nacional de Desarrollo Científico, Tecnologico y de Innovación Tecnológica (PE) [179-2015-FONDECYT].